Presentations in action : 80 memorable presentation lessons from the masters - Weissman, Jerry (FT Press, 2011)
"...Weissman has spent 20 years helping top executives succeed in the most important business presentations of their lives. Here's what he's learned: The best way to get his message across is to show his techniques in action. In Presentation in Action, Weissman does just that: he teaches how to make spectacularly successful presentations by showing exactly how great presenters have done it. Each of the book's 80 chapters dives into the techniques of great presenters to give readers methods that can be put to use immediately. In each chapter, Weissman shares examples from well known figures in politics, science, music, media, sports, And The military, including comedians Johnny Carson and Jon Stewart, politicos Ted Sorensen and Jeffrey Toobin, literature's Mark Twain, and Hollywood's Mike Nichols to name a few..."--Jacket